Urban unemployment in Kerala: the case of Kochi city - Prakash, B.A. (2002)
This study examines the incidence, type and characteristics of urban employment in Kerala's second largest city, and to offer some clues to explain the high rate of joblessness. According to the results of a sample survey, the urbanisation of Kochi has been associated with a process of casualisation of labour, and failure to generate rapid growth of regular employment in the modern organised sector. Besides, joblessness is found to be basically a problem of educated youth, leading to their migration to other parts of India and abroad in search of employment. - Reproduced.
Keywords: Unemployment - India - Kerala; Unemployment